Measurement of Primary and Secondary Stability of Dental Implants by Resonance Frequency Analysis Method in Mandible. (13th May 2013) - Shokri, Mehran; Daraeighadikolaei, Arash
Abstract : Background. There is no doubt that the success of the dental implants depends on the stability. The aim of this work was to measure the stability of dental implants prior to loading the implants, using a resonance frequency analysis (RFA) by Osstell mentor device. Methods. Ten healthy and nonsmoker patients over 40 years of age with at least six months of complete or partial edentulous mouth received screw-type dental implants by a 1-stage procedure. RFA measurements were obtained at surgery and 1, 2, 3, 4, 5, 7, and 11 weeks after the implant surgery. Results. Among fifteen implants, the lowest mean stability measurement was for the 4th week after surgery in all bone types. At placement, the mean ISQ obtained with the magnetic device was 77.2 with 95% confidence interval ( CI ) = 2.49, and then it decreased until the 4th week to 72.13 (95% CI = 2.88 ), and at the last measurement, the mean implant stability significantly (P value < 0.05 ) increased and recorded higher values to 75.6 (95% CI = 1.88 ), at the 11th week. Conclusions. The results may be indicative of a period of time when loading might be disadvantageous prior to the 4th week following implant placement. These suggestions need to be further assessed through future studies.